Abscopal Effects in Radio-Immunotherapy—Response Analysis of Metastatic Cancer Patients With Progressive Disease Under Anti-PD-1 Immune Checkpoint Inhibition - Trommer, Maike; Yeo, Sin Yuin; Persigehl, Thorsten; Bunck, Anne; Grüll, Holger; Schlaak, Max; Theurich, Sebastian; von Bergwelt-Baildon, Michael; Morgenthaler, Janis; Herter, Jan M.; Celik, Eren; Marnitz, Simone; et al. (Frontiers in Pharmacology, 2019)
Immune checkpoint inhibition (ICI) targeting the programmed death receptor 1 (PD-1) has shown promising results in the fight against cancer. Systemic anti-tumor reactions due to radiation therapy (RT) can lead to regression of non-irradiated lesions (NiLs), termed “abscopal effect” (AbE). Combination of both treatments can enhance this effect. The aim of this study was to evaluate AbEs during anti-PD-1 therapy and irradiation. We screened 168 patients receiving pembrolizumab or nivolumab at our center. Inclusion criteria were start of RT within 1 month after the first or last application of pembrolizumab (2 mg/kg every 3 weeks) or nivolumab (3 mg/kg every 2 weeks) and at least one metastasis outside the irradiation field. We estimated the total dose during ICI for each patient using the linear quadratic (LQ) model expressed as 2 Gy equivalent dose (EQD2) using α/β of 10 Gy. Radiological images were required showing progression or no change in NiLs before and regression after completion of RT(s). Images must have been acquired at least 4 weeks after the onset of ICI or RT. The surface areas of the longest diameters of the short- and long-axes of NiLs were measured. One hundred twenty-six out of 168 (75%) patients received ICI and RT. Fifty-three percent (67/126) were treated simultaneously, and 24 of these (36%) were eligible for lesion analysis. AbE was observed in 29% (7/24). One to six lesions (mean = 3 ± 2) in each AbE patient were analyzed. Patients were diagnosed with malignant melanoma (MM) (n = 3), non-small cell lung cancer (NSCLC) (n = 3), and renal cell carcinoma (RCC) (n = 1). They were irradiated once (n = 1), twice (n = 2), or three times (n = 4) with an average total EQD2 of 120.0 ± 37.7 Gy. Eighty-two percent of RTs of AbE patients were applied with high single doses. MM patients received pembrolizumab, NSCLC, and RCC patients received nivolumab for an average duration of 45 ± 35 weeks. We demonstrate that 29% of the analyzed patients showed AbE. Strict inclusion criteria were applied to distinguish the effects of AbE from the systemic effect of ICI. Our data suggest the clinical existence of systemic effects of irradiation under ICI and could contribute to the development of a broader range of cancer treatments.